2019
DOI: 10.12998/wjcc.v7.i9.1038
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic appendectomy for elemental mercury sequestration in the appendix: A case report

Abstract: BACKGROUND Despite negligible absorption of elemental mercury after acute ingestion, retention in the appendix with subsequent local and systemic complications is possible. We present a case of elemental mercury sequestration in the appendix, managed by laparoscopic appendectomy. CASE SUMMARY A 57-year-old Caucasian female was found unconscious following application of long-lasting insulin detemir and ingestion of elemental mercury in a suicidal attempt. Diagnostic inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 13 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…13 Elemental mercury sequestration in the appendix may cause local complications, such as acute appendicitis or perforation, which is considered the third most common sequela of appendicitis. 3 However, in our literature review, we found few studies describing the active management of elemental mercury retained in the appendix. 1,8…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…13 Elemental mercury sequestration in the appendix may cause local complications, such as acute appendicitis or perforation, which is considered the third most common sequela of appendicitis. 3 However, in our literature review, we found few studies describing the active management of elemental mercury retained in the appendix. 1,8…”
Section: Discussionmentioning
confidence: 90%
“…In particular, elemental mercury that remains in the appendix can cause appendicitis and subsequent local complications. 13 Inorganic or organic compounds transformed from elemental mercury could result in chronic toxic effects, such as toxic nephropathy or neurotoxicity, that can persist for decades. 46 Therefore, residual elemental mercury in the body requires immediate attention, even after active conservative treatments.…”
Section: Introductionmentioning
confidence: 99%
“…We report the first case of elemental mercury ingestion that occurred as a result of using a folk remedy, with subsequent retention of mercury in the appendix causing appendicitis that leads to peritonitis. Approximately 12 similar cases of mercury sequestration in the appendix and only three cases of appendicitis related to elementary mercury are found in the literature [7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Any of the foregoing factors can contribute to mercury being arrested in the cecum during transit and gravitating toward the lower portion of the appendix. In this location, peristalsis motion is usually insufficient to expel the mercury thereby causing sequestration [7,20]. As a result, elementary mercury may remain immobile in the appendix, stimulating an inflammatory reaction with the possibility of perforation leading to peritonitis [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation